2013
DOI: 10.1186/1471-2431-13-141
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with asthma among under-fives in Mulago hospital, Kampala Uganda: a cross sectional study

Abstract: BackgroundAsthma is the most common chronic childhood illness, with rapidly increasing prevalence in low-income countries. Among young children, asthma is often under-diagnosed.We investigated the factors associated with asthma among under-fives presenting with acute respiratory symptoms at Mulago hospital, Uganda.MethodsA hospital-based cross sectional study of 614 children with cough and/or difficult breathing, and fast breathing, was conducted between August 2011 and June 2012. A questionnaire focusing on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 34 publications
(49 reference statements)
2
21
0
Order By: Relevance
“…Our observation that children with asthma were more likely to have parents with tertiary education and to use gas or electricity for indoor cooking (as opposed to charcoal stoves) has been made by an earlier study in Uganda (14). Similarly, our finding that children with asthma reported the highest frequency of 'trucks passing on the street near their home' has been reported elsewhere (34)(35)(36).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our observation that children with asthma were more likely to have parents with tertiary education and to use gas or electricity for indoor cooking (as opposed to charcoal stoves) has been made by an earlier study in Uganda (14). Similarly, our finding that children with asthma reported the highest frequency of 'trucks passing on the street near their home' has been reported elsewhere (34)(35)(36).…”
Section: Discussionsupporting
confidence: 76%
“…The few studies reported have suggested that current residence in urban areas is associated with a higher risk of asthma than rural residence (10,11). Other risk factors, similar to those in HICs, include maternal smoking (12,13), maternal history of asthma (14), childhood atopic sensitisation (11,15) and history of allergy (14,16). Previous reports suggest no association between biomass fuels and asthma risk (17,18), but increased asthma symptoms (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…The children who had chest in-drawing were admitted and followed up to determine outcomes. The details of the laboratory methods have been described elsewhere [ 27 ]. Briefly; blood culture, total and differential white cell counts, and serum C-reactive protein (CRP) titres were done.…”
Section: Methodsmentioning
confidence: 99%
“…The association between helminth infections and asthma has been investigated in Africa and other LMICs, but the findings have been inconsistent across studies (Leonardi-Bee et al, 2006; Mpairwe and Amoah, 2019). Other risk factors for asthma in Africa and other LMICs, similar to those in HICs, include maternal smoking (Ayuk et al, 2018; Arrais et al, 2019), maternal history of asthma (Nantanda et al, 2013), childhood atopic sensitisation (Addo-Yobo et al, 2001; Nyembue et al, 2012) and history of allergy (Nantanda et al, 2013; Mehanna et al, 2018). Previous reports suggest no association between biomass fuels and asthma risk (Thacher et al, 2013; Oluwole et al, 2017a), but increased asthma symptoms (Oluwole et al, 2017a; Oluwole et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports suggest no association between biomass fuels and asthma risk (Thacher et al, 2013; Oluwole et al, 2017a), but increased asthma symptoms (Oluwole et al, 2017a; Oluwole et al, 2017b). Unlike in HICs, higher parental education and socioeconomic status has been associated with asthma among children in Africa (Addo-Yobo et al, 2007; Nantanda et al, 2013; Wolff et al, 2012).…”
Section: Introductionmentioning
confidence: 99%